(untitled) (Journal of Civil Engineering Researchers, 2024)
Buildings with masonry materials are one of the weakest buildings against earthquakes, and the importance of proper design and correct construction of these buildings is not hidden. Among The buildings with masonry materials, the buildings with Ring beams are the most common of such buildings. Engineers use internal and external regulations and standards to design ring beam masonry buildings. The two main references for the design and construction of masonry buildings with Ring beams are the Code of Practice for Seismic Resistant Design of Buildings (Standard 2800, Fourth Edition) and the Eighth Topic of the National Building Regulations (2020 Edition) under the title of design and construction of buildings with masonry materials. The Provisions for masonry buildings with Ring beams are given in the fifth chapter of the Eighth Topic of the National Building Regulations and the Seventh Chapter of the 2800 Standard. In this research, an attempt was been made to examine the Provisions of masonry buildings with Ring beams of these two references and to identify the discrepancies and differences in the provisions. The investigation of these two references has shown that there were more than 66 cases of differences in Provisions regarding masonry buildings with Ring beams between the Eighth Topic of the National Building Regulations and the Seismic Resistant Design of Buildings. Most of the differences in the criteria were related to the sections of vertical and horizontal Ring beams, structural walls, and Non-structural walls with 34 cases and 51.5% compared to the total difference. Also, the type of soil is classified in the Eighth Topic of The National Construction Regulations with 3 types of soil and the 2800 Standard of Conduct is classified with 4 types of soil.